2016
DOI: 10.1039/c6dt02186g
|View full text |Cite
|
Sign up to set email alerts
|

Potential applications of polyoxometalates for the discrimination of human papillomavirus in different subtypes

Abstract: The binding-induced luminescence enhancement of an Eu-containing polyoxometalate (POM), EuSiWMo, by the arginin/lysine-rich cationic peptides supplied a platform to detect the capsid proteins of human papillomaviruses (HPVs). However, the strong binding affinity between them makes it very difficult to be differentiated among peptides from different subtypes of HPVs. Therefore, several strategies to monitor the binding affinity of POM-peptide are performed and finally the discriminations on representative pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…[16] In turn, thesei nteractions were recognized to be influencedb yt he electrostatic charge of the POM, its size and shape in host-guesti nteractions, and its composition. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Recently,t he affinity of POMs towards biomolecules have been attributed to the superchaotropic character of the POM anion, providing ab roader descriptiono f the physicochemical foundations of POM-protein interactions. [17] In chaotropic anions, typicallyl arge and charge-delocalized, the ion-dipole interaction with the solventi sl ess directional, and therefore, the desolvation processu pon binding does not change the bulk water structure in large extent reducingt he entropyp enalty.F or example, Nadjo and co-workers found this thermodynamic fingerprint in the binding of Keggin [H 2 W 12 O 40 ] 6À anion to human serum albumin (HSA) protein, where the bindingr eaction is enthalpically driven (DH = À50 kJ mol À1 )w ith as mall, unfavorable entropy component (TDS = À12 kJ mol À1 )d ue to the minimal dehydration entropy change.…”
Section: Introductionmentioning
confidence: 99%
“…[16] In turn, thesei nteractions were recognized to be influencedb yt he electrostatic charge of the POM, its size and shape in host-guesti nteractions, and its composition. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Recently,t he affinity of POMs towards biomolecules have been attributed to the superchaotropic character of the POM anion, providing ab roader descriptiono f the physicochemical foundations of POM-protein interactions. [17] In chaotropic anions, typicallyl arge and charge-delocalized, the ion-dipole interaction with the solventi sl ess directional, and therefore, the desolvation processu pon binding does not change the bulk water structure in large extent reducingt he entropyp enalty.F or example, Nadjo and co-workers found this thermodynamic fingerprint in the binding of Keggin [H 2 W 12 O 40 ] 6À anion to human serum albumin (HSA) protein, where the bindingr eaction is enthalpically driven (DH = À50 kJ mol À1 )w ith as mall, unfavorable entropy component (TDS = À12 kJ mol À1 )d ue to the minimal dehydration entropy change.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several strategies for monitoring the POM–peptide interactions and improving the detection of recombinant HPV capsid protein were also proposed. Subsequently, three europium substituted POMs, [Eu(SiW 10 MoO 39 ) 2 ] 13− (EuSiWMo), [Eu(PW 11 O 39 ) 2 ] 11− (EuPW11) and [EuW 10 O 36 ] 9− (EuW10) with different surface charges were used to discriminate the subtypes of HPV L1 protein [33] . The results showed that EuW10 containing nine negative charges was sufficient to discriminate different subtypes of HPV peptides owing to the specific sequence and basic charge differences.…”
Section: Biological Nanoprobesmentioning
confidence: 99%
“…[ 254 ] Following this observation, the authors developed an in vitro fluorescent sensor to detect the positively charged HPV peptides by using POMs to discriminate the different subtypes of HPV capsid proteins. [ 255,256 ] In addition, they used the ionic coassembly as a probe to precisely identify cell receptor glycosaminoglycans according to competitive recognition among them, which was verified by ITC and luminescence detection. [ 257 ] However, Xin and co‐workers found that the ionic coassembly of EuW 10 and octa‐lysine peptide caused the reduced luminescence of EuW 10 .…”
Section: Cationic Peptides and Polyoxometalatesmentioning
confidence: 99%